THE EFFECT OF WORKLOAD AND WORK STRESS ON EMPLOYEE PERFORMANCE AT HOTEL VERTU & YELLO HARMONI CENTRAL JAKARTA - Riawan, Devit (JURNAL ASIK, 2025)
This study aims to determine the effect of workload and job stress on employee performance, both partially and simultaneously. The background of this research is based on the importance of managing workload and stress in increasing human resource productivity. The method used in this study was a quantitative method with a multiple linear regression approach. Data were collected through questionnaires distributed to respondents and analyzed using t-tests, F-tests, and the coefficient of determination (R²). The results showed that workload had a positive and significant effect on employee performance, with a calculated t-value of 8.725 > t-table 1.985 and a significance level of 0.000 < 0.05. Work stress also significantly influenced performance, with a calculated t-value of 2.489 > t-table 1.985 and a significance level of 0.015 < 0.05. Simultaneously, workload and job stress significantly influenced performance, with a calculated F-value of 38.275 > F-table 3.09 and a significance level of 0.000. The coefficient of determination (R²) of 0.584 indicates that 58.4% of the variation in performance can be explained by the two independent variables, with the remainder influenced by other factors. This finding confirms the need for organizational management to consider balancing workload and stress management to improve employee performance. This research also contributes to the development of human resource management science, particularly in the context of the influence of psychological and operational factors on work outcomes.